THE ROLE OF INTERNET OF THINGS (IOT) TECHNOLOGY IN BUILDING A REAL-TIME COSTING SYSTEM FOR ADDRESSING VARIANCES IN SUSTAINABLE SUPPLY CHAIN COSTS AND ENHANCING COST REPORTING: AN APPLIED STUDY IN THE STATE COMPANY FOR THE PHARMACEUTICAL INDUSTRY AND MEDIC (World Economics and Finance Bulletin, 2025)
This study assesses the feasibility of designing an IoT-enabled system to facilitate the construction and operation of a real-time costing system that models fluctuations in supply chain process costs and enables their real-time monitoring within a sustainable supply chain. This encourages pharmaceutical companies and other industrial companies to improve the accuracy and quality of their cost reporting, since it is an important factor in making decisions. Ministry and tax and other topics otherwise addressed in the Heaven on Earth philosophy, they are Characteristics include control over the actual benwafa. Vote Type in the State Based Company for the Pharmaceutical market and Medical Items capstone, both due to the peculiarities of the project work, and due to elements Artificial social investment. This study employed a descriptiveanalytical and applied methodology utilizing a questionnaire, document analysis, and an interview. We presume the integration of sensors and IoT technology throughout the supply chain stages and present a methodology that facilitates real-time cost calculation based on standard costs. The integration of IoT makes it possible to keep track of average cost deviations and hold people accountable in real time, which makes things much more efficient. The ratio of making accounting reports and having fewer resources for managing other processes through this kind of supply chain segregation makes the process more sustainable and open, cutting costs, time, and waste while improving how resources are used. The goal is to make sure that this digital backbone can quickly add new technologies to current processes. It shows how the IOT could be combined with traditional costing methods. Organizations may see how resources are being used, how much output is going through, and how much variable cost there is in real time by linking physical assets, machines, and operating systems to a larger number of sensors and smart devices. This change lets businesses go from doing cost analysis only once in a while or looking back to doing it on a regular basis and using it to improve resource allocation and costs. The study also shows that staff has to be taught and trained in order to take use of these technological opportunities. Employees ought to comprehend this information, identify trends, and react to a developing trend instantaneously